Prediction of sediment yield of the Inxu River catchment (South Africa) using the MUSLE - David Gwapedza; Namso Nyamela; Denis Arthur Hughes; Andrew Robert Slaughter; Sukhmani Kaur Mantel; Benjamin van der Waal (International Soil and Water Conservation Research, 2021)
The proposed site for the construction of a new dam (Laleni Dam) on the Tsitsa River in the Eastern Cape, South Africa falls within a high soil erosion zone, which is expected to affect the lifespan of the dam. Estimating the sediment yield of the catchment is important from a management perspective, and thus we designed this study to assess the applicability of the Modified Universal Soil Loss Equation (MUSLE). The original MUSLE was applied to the Inxu River sub catchment, upstream of a proposed dam, over a summer rainfall period extending from October 2016 to April 2017. A modified version of the MUSLE, incorporating a storage module, was later applied over the same period. Model calibration of the MUSLE with and without a storage model was tested against 7 months of recorded daily suspended sediment discharge data. With a storage model, we achieved a percentage bias, coefficient of efficiency and R2 of 2%, 0.83 and 0.83, respectively, while without storage the performance statistics were markedly lower. These results suggest that a calibrated MUSLE can provide estimates of sediment yield that are valuable for regional planning, and that the inclusion of a storage component further improves the MUSLE application. Given the complexity of sediment generation and transport processes, a relatively simple empirical MUSLE model is a useful tool for initial sediment yield estimation for planning purposes.